Effect of high temperature stress on the reproductive growth of straberry cvs. 'Nyoho' and Toyonoka' - Ledesma, Nadine Adellia A. (Animo Repository, 2008)
High temperatures are known to reduce fruit size and fruit weight in strawberry, but cultivar differences in the response to high temperature stress during the reproductive stage up to the second inflorescence have not been sufficiently reported. We examined the effect of two day/night temperature regimes on fruit set and fruit growth in two cultivars, 'Nyoho' and 'Toyonoka'. A high day/night temperature of 30/25 °C reduced the number of inflorescences, flowers, and fruits in both cultivars compared with plants grown at 23/18 °C. The percentage of fruit set in 'Nyoho' was not significantly different between the two temperature treatments, while that in 'Toyonoka' was much lower at 30/25 °C than at 23/18 °C. Days to ripening was shorter at 30/25 °C than at 23/ 18 °C, and no cultivar differences were observed. Fresh weight of primary, secondary, and tertiary fruits was greater at 23/18 °C than at 30/25 °C in both cultivars, and no cultivar differences were observed, except in tertiary fruits. The diameter of fruits from all positions was also reduced at 30/25 °C in both cultivars. Relative growth rates of fruits showed two peaks in both cultivars and in both temperature treatments. Both peaks appeared earlier at 30/25 °C than at 23/18 °C. Percentage of fruit set at 30/25 °C in the second inflorescence was also significantly lower in 'Toyonoka' than in 'Nyoho'. These results indicate that high temperature stress negatively affects the reproductive process in strawberry and that plant response to high temperature stress is cultivar-related in such responses. © 2008 Elsevier B.V. All rights reserved.